Parking Arrangement for Business Area on Pemuda Street in Medan City - Siregar, Syafiatun; Hafizh, Alif Muhammad; Barlian, Edo; Solahuddin, Ahmad Andi (Universitas Negeri Padang, 2024)
The purpose of the parking arrangement is: a) to determine the parking system on the Jalan Pemuda Medan City section; b) to organize and simulate parking in the business area of Jalan Pemuda, Medan City. The results are as follows: a) The existing Static Capacity is 41 SRP on the left side and the right side is 62 SRP; b) Section A parking duration is 1.28 hours and 1 hour. Section B is 1.85 hours and 1.14 hours; c) The dynamic capacity of Section A is 144 SRP and 247 SRP. Section B is 137 SRP and 238 SRP; d) The parking volume on Jalan Pemuda section A is 27 and 36 passenger cars. Section B as many as 37 and 39 passenger cars; e) Section A parking index is 71.42% and 58.33%, in Section B is 95% and 73.53%; f) Turn Over in section A is 1.3 vehicles/space and 1 vehicle/space, in section B it is 1.85 vehicles/space and 1.14 vehicles/space; g) Optimizing the parking length from 205 meters to 210 meters. The parking arrangement on Jalan Pemuda has 4 alternatives, namely 1) the shape of the parking angle remains but the parking length increases from 205 meters to 210 meters; 2) change the existing parking angle of 00 in the left lane and 450 in the right lane to 450 for the right and left lanes; 3) both right sides change with the shape of the parking angle to 600; 4) change the parking angle to 300 so that it can increase static capacity.